A Single Case Study Of Ayurvedic Management Of Ankylosing Spondylitis W.S.R. To Amavata - Joshi, Falguni; Sharma, Ravi; Zahir, Ruhi (International Research Journal of Ayurveda & Yoga, 2021)
Ankylosing spondylitis (AS) is a type of rheumatic disease known as spondyloarthropathies (SpA), and it has a significant link to the HLA-B27 genetic marker. The involvement of spinal joints, particularly the sacroiliac joint, is gradual and insidious. Inflammatory back pain and stiffness are common in the early stages of the disease, but in the later stages of the disease, severe pain and axial immobility or deformity can occur. In this disease, the lack of a successful biomedical treatment results in irreversible malformation. In these instances, several Panchakarma procedures and Ayurvedic medications have shown to be beneficial. The therapy includes rigorous dietary restrictions as well as lifestyle changes. The Ayurvedic method aims to reduce disability while also easing symptoms. Here, we discuss a case of Amavata that was effectively treated with Ayurvedic medicine.